A New Production Forecasting Method of the Multifractured Horizontal Wells Based on Cluster Analysis. (27th October 2021) - Lu, Mingjing; Wang, Zenglin
Abstract : The seepage mechanism of multifractured horizontal wells is complex in tight reservoirs, which make that the production is very difficult to forecast. This article put forward a new way called the developed clustering analysis to forecast well production which is based on the practical production data of 10 multifractured horizontal wells. This method first uses the information analysis method to obtain the weight of the influencing factors of horizontal well production and normalizes the influencing factors of production. Second, the feature matrix is constructed by combining the weight of each factor, and the distance between the feature matrix of different production wells and the optimal feature matrix is calculated. Finally, the relationship curve between distance and production is plotted, and the production chart of the block is obtained. Taking 9 multifractured horizontal wells in the tight reservoir as an example, the production prediction chart of the block is calculated. At the same time, the production data of the 10th well are used to verify the production chart of the block. The results show that the horizontal well production has a high fitting relationship with the distance. The error between the new well production predicted by the chart and the actual production is 4.7%, which meets the requirements of the field error. The model was also used in a reservoir with 154 wells and also verified the accuracy of the model. The prediction method proposed in this paper can accurately predict the production of volume fractured horizontal wells in the experimental area and provide certain guiding significance for the development and adjustment of tight reservoirs.